(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Limestone waste is a byproduct of the aggregate production process in the rubble crusher Limestone unit, which involves the crushing of rocks. The use of limestone waste as a sand substitute in construction materials would alleviate the environmental problems created by the large-scale depletion of natural sand sources such as river and mining sands. Every year, millions of tonnes of waste glass are produced around the world. Glass is disposed of in landfills once it becomes a trash, which is unsustainable because it decomposes in the environment. The use of various coloured glass powder as a partial sand substitute could be a critical step toward the creation of long term infrastructure systems. Fly ash is the bound residue of coal’s clay mineral deposits. most of which are aluminum silicate in compositionhappens as a result of high temperatures generated during coal combustion in thermal power plants. To improve the properties of Portland cement concrete fly ash used. The purpose of this experiment was to see how fractional replacement of sand with lime stone waste powder[LSW], different coloured glass powder, and cement with Fly ash affected the several fresh and cured qualities of concrete. So, in my research, I’m utilising M30 grade and a constant mix of different coloured glass powder in sand. Workability tests, compressive strength testing, and split tensile tests were performed to determine the ideal combination that results in the highest percentage of strength.